Effect of Special Exercises According to Skill Performance Endurance to Develop Some Physical Abilities and Scoring With the Head Accuracy Skill by Jumping among Talented of the Amo Baba Football Academy for the Ages of (14-15) Years in Football - Al-Jubori, Muhammad Ghani Hussain (Journal of Innovation in Education and Social Research, 2024)
This research dealt with the preparation of special exercises to withstand the skill performance in the development of some physical abilities in the accuracy of the skill of scoring with the head of jumping and to identify the impact of these exercises in the development of physical abilities such as motor speed and explosive power of the legs and rapid force, so the researcher used the experimental approach according to exercises to withstand the skill performance and that for its suitability to conduct field research because it is the best approach to suit the nature of the problem and reach the goal. Therefore, the researcher applied the vocabulary of the exercises for a period of (8) weeks by (2) training units per week (Friday - Tuesday), if the ability to withstand the skill performance in developing capabilities is placed accurately scoring with the head of jumping for the sample members. As a result of the efficiency of the training curriculum prepared by the researcher. It witnessed the improvement of the level of performance in the post-tests of the experimental group as a result of the increased development of physical capabilities according to the endurance of the skill performance and the effectiveness of the program for these exercises, where the researcher concluded the superiority of the experimental group in the post-tests of physical abilities and the accuracy of the skill of hitting the ball with the head from the jumping under study, as well as the research concluded the extent of the impact of bearing skill performance in the development of abilities under study accurately scoring with the head of jumping according to this approach, as the researcher recommended the need to legalize the training load for training programs To work on training to withstand skill performance to avoid defects in the training unit in the development of physical abilities and accuracy of the skill of scoring head from jumping to the research sample.